2004
DOI: 10.1037/0735-7044.118.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Operant Escape and Innate Reflex Responses to Nociceptive Skin Temperatures Produced by Heat and Cold Stimulation of Rats.

Abstract: In behavioral tests, rats performed learned escape responses to thermal stimulation of the paws by 44.0. 47.0. or 0.3 degrees C. Licking, guarding, and jumping reflexes were evaluated at these temperatures. The frequency, latency, and duration of escape and reflex responses were compared and were related to hind-paw skin temperatures measured during stimulation of awake and anesthetized rats. The duration and latency of escape from heat were appropriately related to stimulus intensity. Escape occurred reliably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 22 publications
1
41
0
1
Order By: Relevance
“…High drug doses could also interfere with operant measures but these are detectable with the OPAD 6 . Other studies have also demonstrated that the thresholds for escape from a painful stimulus are different for operant versus reflex-based measures 29,2,30 suggesting a major difference between an animals' perception of pain versus the speed of their spinal reflexes. A benefit of the OPAD is that the rodent can choose whether or not to perform the task, this allows the rodent to express escape or avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High drug doses could also interfere with operant measures but these are detectable with the OPAD 6 . Other studies have also demonstrated that the thresholds for escape from a painful stimulus are different for operant versus reflex-based measures 29,2,30 suggesting a major difference between an animals' perception of pain versus the speed of their spinal reflexes. A benefit of the OPAD is that the rodent can choose whether or not to perform the task, this allows the rodent to express escape or avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A benefit of the OPAD is that the rodent can choose whether or not to perform the task, this allows the rodent to express escape or avoidance behavior. This complex behavior requires cortical decision making to control the amount of nociception the rodent feels 14,29,15,30 . While escape and avoidance behaviors can interfere with reflex based measures these pain behaviors are an integral component of the OPAD.…”
Section: Discussionmentioning
confidence: 99%
“…A modified hotplate test, as described previously, was used to assess effects of depletion of MOR-expressing dorsal horn neurons on innate spinal brainstem-spinal nocifensive reflex responses to noxious thermal stimuli (Vierck et al, 2004). In brief, before any testing, rats were acclimated to the room temperature test chamber, which consisted of a clear Plexiglas box (30 ϫ 30 ϫ 15 cm) with a ventilated lid sitting on a custom-built aluminum plate containing internal circulation channels to assure uniform surface temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Phasic thermal pain in humans and thermal operant escape responses in animals to lower-intensity thermal stimuli produce sensations and nocifensive responses dominated by input from unmyelinated C nociceptors (Yeomans and Proudfit, 1996) that are highly sensitive to attenuation by systemic morphine (Cooper et al, 1986;. C nociceptors are preferentially activated by lower-intensity stimuli, 43-45°C (Vierck et al 2004). The present study seeks to determine whether selectively destroying dorsal horn MORexpressing neurons differentially alters morphine effects on nocifensive reflex responses to preferential activation of C thermal nociceptors (44°C) versus A-␦ thermal nociceptor activation (52°C).…”
Section: Introductionmentioning
confidence: 99%
“…Allchorne et al (2005), who defined cold threshold in normal rats at 5°C, and Jasmin et al (1998), who reported nocifensive behaviors Ͻ3°C. Using operant assays, Vierck et al (2004) reported thresholds for "lick/guard/jump" behaviors at ϳ4°C; however, escape behaviors were observed at much warmer temperatures (ϳ16°C).…”
Section: Neural Mechanisms Of Cold Somatosensationmentioning
confidence: 99%